2021
DOI: 10.1016/j.ijbiomac.2021.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis enhancement using poly (l-lactide-co-d, l-lactide)/poly (vinyl alcohol) nanofibrous scaffolds reinforced by phospho-calcified cellulose nanowhiskers

Abstract: This work aim is to develop hydrophilic and biodegradable nanofibrous scaffolds for bone tissue engineering based on poly (L-lactide-co-D, L-lactide) (PLDLLA) and poly (vinyl alcohol) (PVA) reinforced by phospho-calcified cellulose nanowhiskers (PCCNWs). PCCNWs with inherent hydrophilic properties enhanced the mechanical properties, hydrophilicity and hydrolytic degradation of the nanofibrous.Moreover, calcium phosphate and phosphate functional groups on the surface of PCCNWs possessing act as stimulating agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Blending PLA with biopolymers such as cellulose improves the properties of PLA without altering its biocompatibility. PLA/cellulose composites have been widely developed and studies on structural, thermal and mechanical properties have been reported 12,[44][45][46][47][48][49][50][51] . However, even though PLA and cellulose nanocomposites are reported in the literature for tissue engineering applications, we believe that there is still room to develop 3D scaffolds for tissue engineering by FDM which is a rapid and low-cost additive manufacturing technique especially to overcome certain limitations encountered in the PLA, namely the mechanical resistance of the biopolymer.…”
mentioning
confidence: 99%
“…Blending PLA with biopolymers such as cellulose improves the properties of PLA without altering its biocompatibility. PLA/cellulose composites have been widely developed and studies on structural, thermal and mechanical properties have been reported 12,[44][45][46][47][48][49][50][51] . However, even though PLA and cellulose nanocomposites are reported in the literature for tissue engineering applications, we believe that there is still room to develop 3D scaffolds for tissue engineering by FDM which is a rapid and low-cost additive manufacturing technique especially to overcome certain limitations encountered in the PLA, namely the mechanical resistance of the biopolymer.…”
mentioning
confidence: 99%
“…Based on the sessile drop method, a water contact angle (WCA) was performed to evaluate the hydrophilicity of PCL/CA nanofibrous samples with and without kiwi extract 34 . WCA values were measured with a G-10 contact goniometer (Kruss, Germany) using a water droplet dispersed on the sample's surface (n=3).…”
Section: Water Contact Angle Analysismentioning
confidence: 99%
“…Both polymers (PLA and PCL) degrade via cleavage of ester bonds of their backbone and change into acidic monomer that can accelerate the degradation process, and this acidic monomer can be disposed of by normal metabolic pathways from the body. The degradation rate of PLA and PCL is controlled by various factors such as molecular weight, crystallinity, temperature, absorbed water, and solubility of the degradation products (Sung, Meredith et al 2004, Ghaffari-Bohlouli, Zahedi et al 2020, Ghaffari-Bohlouli, Jafari et al 2021.…”
Section: Accelerated Degradation and Biodegradationmentioning
confidence: 99%
“…Potential weak physical interactions between the PLA and PCL could be attributed to the observed shifts in the FTIR spectra of the scaffolds (Lu and Kazarian 2020).Table1. The FTIR spectra peak assignments of functional groups for the PLA, PCL, and PLA-PCL(Fang, Zhang et al 2010, Ghaffari-Bohlouli, Zahedi et al 2020, Ghaffari- Bohlouli, Jafari et al 2021.…”
mentioning
confidence: 99%